Guidelines for the Management of Pediatric Severe Traumatic Brain Injury, Third Edition: Update of the Brain Trauma Foundation Guidelines. (March 2019) - Kochanek, Patrick M.; Tasker, Robert C.; Carney, Nancy; Totten, Annette M.; Adelson, P. David; Selden, Nathan R.; Davis-O'Reilly, Cynthia; Hart, Erica L.; Bell, Michael J.; Bratton, Susan L.; Grant, Gerald A.; Kissoon, Niranjan; et al.
Abstract : Supplemental Digital Content is available in the text.